MENINGKATKAN KEMAMPUAN GURU MENERAPKAN MODEL KERJA KELOMPOK UNTUK MENINGKATKAN HASIL BELAJAR SISWA MELALUI TEKNIK SUPERVISI KUNJUNGAN KELAS - Lisnawaty Sinaga (JURNAL TEMATIK, 2019)
The purpose of this study is to find out through classroom visit supervision techniques that can improve the ability of teachers to apply group work models to improve student learning outcomes in SDN 097320 Serapuh. This school action research was carried out in 2 cycles using classroom visit supervision techniques. Each cycle consists of 2 meetings. The subject of the research was the teacher class of SDN 097320 Serapuh which consisted of 3 students. Data collection methods used written tests in the form, questionnaire observation sheets, and photo results. Based on the results of the study it can be concluded that the average score from the observation of pre-cycle competencies carrying out learning is 61.5 or with sufficient quality and the average score of observations in cycle 1 about competence implementing learning is 71.9 or good quality level. The increase in the average score of pre-cycle, cycle 1 and cycle 2 data is as follows: the results of the cycle 1 score are higher than the pre-cycle data score of 10.37, the results of the cycle 2 score are higher than the cycle 1 score that is equal to 13.9, the results of data score II are higher than the pre-cycle data score of 24.3, from 3 teachers after being supervised twice there was an increase in the ability of teachers to improve their competence in carrying out excellent learning.